Transvenous Atrial Pacing from the Superior Vena Cava Stump after the Hemi‐Fontan Operation—A New Approach. Issue 5 (25th November 2013) - ROSENTHAL, ERIC; KONTA, LAURA
<x xml:space="preserve">Abstract</x> Background The placement of a standard endocardial pacemaker system is challenging after a superior cavopulmonary connection (hemi‐Fontan operation or Glenn shunt) as the continuity between the superior vena cava (SVC) and right atrium is divided. The standard transvenous approach for endocardial lead placement has therefore in general been avoided, and epicardial leads have been placed. Methods In three patients after a hemi‐Fontan procedure, we found viable atrial tissue in the SVC stump of the superior cavopulmonary anastomosis, which was still connected electrically to the right atrium into which active‐fixation leads could be safely implanted. Results There was excellent short‐ and long‐term atrial pacing and sensing characteristics in the SVC stump. Conclusions We describe a technique for transvenous pacing in patients after the hemi‐Fontan procedure using the conventional subclavian vein approach and pectoral placement of the generator. For ventricular pacing, it was possible to cross the patch dividing the right atrium from the SVC either using a spontaneous leak or by needle puncture.